Kota Tua Sebagai Destinasi Wisata Kota: Kenapa Tidak (Implementasi Kebijakan Publik) - Aang Afandi; Dewi Rahayu (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2021)
Cities in Indonesia continue to improve, both physically and non-physically, to become smart cities. This is also the function of the city as the center of activity in a region. On the other hand, some cities have a history with their old cities. This old city asset deserves to be maintained, preserved, and developed as a city tourism destination. This study aims to identify how a city that has old city assets can manage its assets as a city tourist destination, then to identify the potential of cities in Indonesia and to make stages that the city must carry out if it wants to utilize the assets of the old city as a city tourist destination. The study method used is to explore the city in the management of the old town area so that it can get a picture of what is being done by comparing it to several other cities in the world and related to the prerequisites of a destination as city tourism. The results show the stages that can be used as a reference for the city to develop the old city. The results of this study need further deepening, related to the recommended stages and the need for Delphi methods, as a form of FGD with experts in their fields where this activity is indeed multi-scientific background. So that the governance of material and intangible cultural heritage can be achieved without neglecting the various values that must be fulfilled. It is hoped that this phasing can serve as a raw model in the management of the old town (cultural heritage) in other cities